Seismic retrofitting of the historical masonry structures using numerical approach. (15th June 2016) - Akcay, Cemil; Bozkurt, Tarik Serhat; Sayin, Baris; Yildizlar, Baris
Highlights: The laboratory tests and in situ analyses of samples taken from the building have been performed. The numerical analysis of the prepared building model using finite element software have been given. The restoration applications using laboratory, in situ and numerical analysis results have been presented. Abstract: In historical buildings, because of the deterioration on structural members including slab and walls that complete their life cycle in time, due to environmental conditions; restoration applications have become necessary to increase the material durability level and to have adequate level of structural strength in order to resist dynamic effects such as earthquakes. This paper focuses on assessment of historical masonry structures from the point of seismic resistance. The entire process is illustrated using case study from a historical masonry structure. In this study conducted in this respect, a historical building is restored within the scope of laboratory studies and numerical analyses. The first stage of the study includes plaster analyses and mechanical tests conducted on the samples taken from the said building. In the second stage, i.e. numerical analysis, the building's existing 3D computer model was prepared and materials, members that are inadequate in terms of strength were determined. The third stage includes restoration applications by using laboratory and numerical analysis results. Within the scope of restoration applications, structural cracks on the walls were repaired using the injection method; volta slab (brick floor arches), exterior facade walls, interior walls and door/window gaps using different techniques were strengthened. In this study, it was aimed to increase material durability and structural strength by using conventional and modern techniques within the scope of laboratory tests and numerical approaches in recovering the historical buildings.